2017
DOI: 10.1016/j.msea.2017.08.112
|View full text |Cite
|
Sign up to set email alerts
|

Twin-assisted precipitation during hot compression of an Mg-Gd-Zn-Zr magnesium alloy

Abstract: Dynamic precipitation in an Mg-Gd-Zn-Zr alloy during hot compression at 350℃ and 450℃ and at strain rates of 0.001-0.1s-1 is investigated. The deformation conditions were designed such as to promote twinning or slip of dislocations. The results indicated that both twinned and non-twinned grains were present at 350℃, with the extent being a function of the applied strain rate. The formation and propagation of {101 ̅ 2}〈1 ̅ 011〉 primary tensile twins within the twinned grains was identified as being at root of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 45 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…This phase has been mentioned in previous studies, mainly for Mg-Gd-Zn alloys. [32][33][34][35] Based on the contents of Zn and RE, slight variations in chemical composition as well as lattice parameters may occur.…”
Section: Center-line Segregationmentioning
confidence: 99%
See 1 more Smart Citation
“…This phase has been mentioned in previous studies, mainly for Mg-Gd-Zn alloys. [32][33][34][35] Based on the contents of Zn and RE, slight variations in chemical composition as well as lattice parameters may occur.…”
Section: Center-line Segregationmentioning
confidence: 99%
“…However, in some Mg-Gd-Zn alloys the (Mg,Zn) 3 Gd or for rare earth containing magnesium alloys the (Mg,Zn) 3 RE phase is reported. [32][33][34] Saadati et al 32 found that the (Mg,Zn) 3 Gd phase precipitates dynamically under compressive load. It was therefore assumed that, as a result of the special solidification conditions in the center of the strip and the combined rolling during TRC of the WZ73 alloy, the (Mg,Zn) 3 Y phase was formed.…”
Section: Channel Segregatesmentioning
confidence: 99%